Efektivitas Teh Rosella (Hibiscus Sabdarif) Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi - Lisa Rahmi; Mia Salsabila; Isni Hijriana (Yayasan Sagita Akademia Maju, 2024)
Hypertension is one of the global health problems that has a significant impact on morbidity and mortality, especially in the elderly. This study aims to determine the effectiveness of rosella tea (Hibiscus sabdariffa) on reducing blood pressure in the elderly with hypertension. The study design used a quasi-experimental design with one group pre-test post-test design, involving 30 respondents who consumed rosella tea twice a day for one week. Data were analyzed using the Wilcoxon test to identification differences in blood pressure before and after the intervention. The results showed a significant decrease in systolic and diastolic blood pressure after giving rosella tea (p < 0.05). Active ingredients such as flavonoids, anthocyanins, and polyphenols in rosella tea contribute to the antihypertensive effect through the mechanism of vasodilation and increased blood vessel elasticity. This study concludes that rosella tea is effective as a safe additional therapy for managing hypertension in the elderly, although further research is needed to validate these results in a wider population.